Emotional intelligence, management of subordinate's emotions, and leadership effectiveness. Issue 5 (2nd July 2018) - Edelman, Peter; van Knippenberg, Daan
Abstract : Purpose: The purpose of this paper is to address two of the major questions in the relationship between emotional intelligence (EI) and leadership effectiveness: does EI conceptualized and assessed as an ability influence leadership effectiveness when controlling for cognitive intelligence and Big Five personality traits? And, what are mediating processes in this relationship? Design/methodology/approach: Ability test data for EI for 84 leaders in an assessment center were used to predict unobtrusive observations of leader responses to subordinate's emotions in a role play, and expert ratings of leadership effectiveness, controlling for cognitive ability and Big Five personality traits. Findings: EI predicted the appropriateness of leader responses to subordinate's emotions, and these responses mediated the relationships of EI and leadership effectiveness, controlling for cognitive ability and Big Five personality traits. Research limitations/implications: The assessment center context represents a relatively artificial environment and follow-up research in field settings would be particularly valuable. Practical implications: EI can be assessed as a selection tool for leadership positions. Leadership development programs can also focus on developing the skills associated with EI. Originality/value: The study provides stronger evidence for the relationship between EI and leadership effectiveness than previous research, bolstering the confidence in conclusions regarding this relationship. The study also contributes to the development of process models of the influence of EI on leadership effectiveness by providing evidence regarding mediation.